The British Museum - Smirke, Robert
Nash was not alone in his stylistic attitudes. These same attitudes were fostered by the Academy Schools, while the continued discovery of archaeological remains accentuated the repertoire of classical design. Roman models were displaced by Greek, and the issues were now largely those of taste. Robert Smirke (1780-1867) is typical of the careful, busy architects who, in this prosperous period, erected many classical public buildings of unquestionable quality. The tradition was to live on in England for another century; but, although respected by the English, it had grown dull. The forces of Romanticism were stirrng, and, when in 1836 Pugin published "Contrasts," the country turned its back on the Renaissance as if it were just another style.